2019
DOI: 10.1016/j.cognition.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of sensorimotor learning reveals phoneme representations in preliterate children

Abstract: Reading acquisition is strongly intertwined with phoneme awareness that relies on implicit phoneme representations. We asked whether phoneme representations emerge before literacy. We recruited two groups of children, 4 to 5-year-old preschoolers (N=29) and 7 to 8year-old schoolchildren (N=24), whose phonological awareness was evaluated, and one adult control group (N=17). We altered speakers' auditory feedback in real time to elicit persisting pronunciation changes, referred to as auditory-motor adaptation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Research has shown that this metalinguistic knowledge is in fact not only necessary for developing fluent reading (review in English: Goswami & Bryant, 2016;in French: Alegria & Mousty, 2004;in German: Fricke et al, 2016;Landerl & Wimmer, 2008), it also contributes to the development of fine-grained perceptual abilities (review in Mayo et al, 2003), and interacts with speech production fluency (Noiray et al, 2019b;Saletta et al, 2016). Noiray et al (2019b) recently found that German children enrolled in the first grade performed better in tasks probing the manipulation of small phonemic units as compared to preliterate children, who only performed well with larger phonological units (e.g., syllables, rimes, see similar findings in preliterate French children : Caudrelier et al, 2019, in English: Morais, 2003; review in Shankweiler & Fowler, 2004). This suggests that phonemic decoding/encoding training in school stimulates children's awareness of the structural combinatoriality of their native language and improves their ability to manipulate various size compounds (e.g., Studdert-Kennedy & Goldstein, 2003;Ziegler & Goswami, 2005).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Research has shown that this metalinguistic knowledge is in fact not only necessary for developing fluent reading (review in English: Goswami & Bryant, 2016;in French: Alegria & Mousty, 2004;in German: Fricke et al, 2016;Landerl & Wimmer, 2008), it also contributes to the development of fine-grained perceptual abilities (review in Mayo et al, 2003), and interacts with speech production fluency (Noiray et al, 2019b;Saletta et al, 2016). Noiray et al (2019b) recently found that German children enrolled in the first grade performed better in tasks probing the manipulation of small phonemic units as compared to preliterate children, who only performed well with larger phonological units (e.g., syllables, rimes, see similar findings in preliterate French children : Caudrelier et al, 2019, in English: Morais, 2003; review in Shankweiler & Fowler, 2004). This suggests that phonemic decoding/encoding training in school stimulates children's awareness of the structural combinatoriality of their native language and improves their ability to manipulate various size compounds (e.g., Studdert-Kennedy & Goldstein, 2003;Ziegler & Goswami, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…This assumption was validated. However, reading fluency involves more complex relationships than speech (e.g., Caudrelier et al, 2019;Mayo et al, 2003;Noiray et al, 2019b;Saletta, 2019). Figure 7 provides a conceptual illustration of those differences.…”
Section: Directionality Of the Speech And Reading Interactionmentioning
confidence: 99%
“…Indeed, syllables produced by 4-year-old children, which are the main units of babbling and of bi-syllabic first words, may still be represented in a holistic manner, for example in the form of a motor program or a gestural score specifically dedicated to the production of a syllable, or they may be represented as a sequence of phonemes, since at this age children are in the middle of a cognitive process transforming their representations from a holistic to one that includes a segmental component (see [28], for a summary of related studies). We hypothesize that in a group of 4-year-old children, coarticulation patterns within a syllable may vary significantly across subjects, since some of the children may be able to control syllables as serial-order motor tasks, whereas others would still rely on a holistic specification, with the possibility that both representations coexist in a subject, with different weights, as suggested by Caudrelier et al (2019) [58].…”
Section: Theoretical Background and Working Hypothesesmentioning
confidence: 95%
“…Working hypotheses. In aiming to compare the speech motor performances of children below age 6 with that of adults, and to explain any observed differences, we chose to study 4-year-old children for two main reasons: (1) it is generally acknowledged that these children have acquired some representations of the phonemes of their language [28,[56][57][58], and (2) from a motor control perspective, based on the studies described earlier, age four is around the onset of a period during which sensorimotor representations are beginning to play an increasing role in motor planning and motor control (see also [45,59]). Consistent with the emergence of phonemic representations at this age, we assume that 4-year-old children have moved, or are in the process of moving, from a relatively simple holistic representation of words [60], suitable for the storage of small lexicons in early development, to a more complex representation in which individual phonemes also play an important role, in later phonological development [61].…”
Section: Theoretical Background and Working Hypothesesmentioning
confidence: 99%
“…Complete answers to both of these questions require that researchers study children from different language environments-children with different receptive and expressive language experiences. In the past, the role of receptive versus expressive experience was evaluated by studying the influence of lexicon size or degree of phonological awareness on speech development (Caudrelier et al 2019;DePaolis, Vihman, and Keren-Portnoy 2011;Noiray et al 2019; but see Mayr, Howells, and Lewis 2015). Here, the role of the language environment for phonetic development is evaluated in a novel way: by studying speech development in a bilingual community undergoing rapid language shift.…”
Section: Introductionmentioning
confidence: 99%